Avaliação competitiva de usos dos recursos hídricos em trechos de gerenciamento de rio: estratégia para subsidiar o licenciamento ambiental - Maziero, Elisandra (2015)
Considering that water is limited and requires appropriate planning to ensure its proper use, pondering future generations as well as the socio-economic development, some impacts may create conflicts among users of the same stretch of river. Currently, the major competing uses in a stretch of river are: hydropower generation, irrigation and use for sewage dilution, additionally the use for ensuring the environment balance. For hydropower generation water is usually repressed and / or diverted from its original course to a lower point resulting in a stretch of river with modified flows. The water used for Irrigation depends on the plant demand and climatic conditions of the region in analysis. Accordingly, the crop productivity is directly related to water availability for the plant. In the use of water for sewage dilution, the sewage treatment conditions are often poor or non-existent, resulting in the flow values for treatment. The proposed paper presents a method for quantifying the impacts among competing uses of water in a stretch of river with modified flows due to a development of hydropower generation. The main study case for this analysis is a stretch of river with modified flows caused by the hydropower Passo São João, in the Ijuí river. Hypothetical scenarios are simulated to evaluate the competitiveness among different uses of water in the stretch of river including demand in irrigation for soy and corn. Also including demand for sewage treatment on the stretch of an urban population. Different regimes of ecological flow are taked as basis for balancing the stretch. Gains and losses in relation to the prices of energy and agricultural production are also considered for the analysis. The described other uses competing with hydropower generation result in different operating rules of the hydropower plant. These rules affect energy production, but lead to the multiple use of water in the stretch. By analysising the outcome of the the proposed simulations it is verified that irrigation caused minor impact on the electricity generation in comparison to sewage dilution, for a population of ten thousand. In addition there is a much larger gain in monetary terms than the loss on the energy that are not generated. This fact provided a strong argument for irrigation competitiveness analysis in the stretch of river. The sewage dilution causes significant losses for electricity generation. However it is a necessary use to compensate poor or nonexistent treatment for sewage dilution. This study presents a generic methodology that can be applied for strategic planning to water rights, evaluating cases where there are conflicts over the multiple uses of water in the presence of hydropower generation. The resulting operation rule for competing uses of water in a stretch of river can be used to support the decision making process for the environmental licensing in a stretch of river with modified flows.